De la controverse à l'acceptabilité sociale : le rôle constructif du conflit - Sofiane Baba; Chantale Mailhot (VertigO)
We live in a context of increasing socio-economic-environmental controversies and growing demand for involvement of civil society in decision making processes related to major development projects. Thus, issues related to the process of construction and reconstruction of relationships between companies and local stakeholders following a controversy are emerging as important objects of study. We are particularly interested in the role of controversies in a so-called socially acceptable approach inquiring how actors can reach an agreement despite deep differences in their values, interests and logics. To do so, we analyze the controversial case of the Great Whale hydroelectric project in depth, a project consisting of three hydropower plants promoted by Hydro-Québec in the late 1980s. On a theoretical level, we rely on the economies of worth approach to reflect on how different actors defend the legitimacy of their position and overcome conflicts. The contribution of this paper is threefold. Theoretically, it consolidates the emerging field of social license to operate by incorporating an unexplored dimension, conflict. By mobilizing the economies of worth framework, it conceptualizes the social license to operate process on a plurality of logics justification and action. It also suggests three mechanisms promoting the social license to operate following a controversy: gradation, devices and bridging practices.